Isabelo’s Nature and Weather: Exploring Isabelo de los Reyes’ Notes on the Physical Environment in the El Folk-Lore Filipino (1889) - Alvarez, Kerby C. (BANWAAN: The Philippine Journal of Folklore, 2025)
In his analysis of Isabelo de los Reyes’ Historia de Ilocos (1890), Ubaldo (2012) makes a case for the historiographical contribution of the work in local historical studies by emphasizing the Ilocano intellectual assertion of the participation of the people in precolonial and colonial developments. In this observation, local and folk beliefs and practices were important objects and subjects of historical knowledge production. However, an earlier work made De los Reyes a trailblazer in historical and cultural studies in the country. His 1889 work, El Folk-Lore Filipino (1889) has been appraised as a pioneer scholarly documentation of Philippine folk knowledge. This paper presents a historical dissection of the El Folk-Lore Filipino and identifies the valuable notes, descriptions, and analyses of the physical environment, found in select sections of the book. This work highlights this specific aspect of De los Reyes’ magnum opus and offers another look into how the documentation of folklores and cultural vignettes can shed light on how local communities make sense and create meanings on nature and the environmental processes related to it. Keywords: Isabelo de los Reyes, physical environment, folk knowledge, local history, knowledge production